Do statin users adhere to a healthy diet and lifestyle?: the Australian Diabetes, Obesity and Lifestyle Study - Johal, Simran; Jamsen, Kris M.; Bell, Simon J.; McNamara, Kevin P.; Magliano, Dianna; Liew, Danny; Ryan-Atwood, Taliesin E.; Anderson, Claire; Ilomäki, Jenni (Sage, 2016)
Background